Genetically modified dendritic cells as a cancer treatment strategy - Mackiewicz, Andrzej; W. Kowalczyk, Dariusz; Mackiewicz-Wysocka, Małgorzata; Grabarczyk, Piotr; J. Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2002)
Dendritic cells (DCs), the most potent APCs have been discovered almost 30 years ago. Due to priming of antigen-specific immune responses mediated by CD4+ and CD8+ lymphocytes, DCs are crucial for the induction of adaptive immunity against cancer. Therefore, vaccination of cancer patients with DCs presenting tumor associated antigens (TAAs) have been believed to be a promising anti-cancer strategy. Until now multiple clinical trials have been carried out in order to evaluate the safety and efficacy of cancer vaccines based on antigen-pulsed DCs. However, pulsing of DCs with particular peptides has several disadvantages: (i) short-time duration of antigen-MHC complexes, (ii) requirement for matching of defined peptides with MHC complexes and (iii) exclusive presentation of single antigen epitopes. Application of gene transfer technologies in the field of DCs-based vaccines made possible the development of novel, anti-cancer immunization strategies. In several animal models, DCs modified with genes encoding TAA or immunostimulatory proteins have been shown to be effective in induction of anti-tumor immune responses. Based on these encouraging results, a first clinical trial of vaccination of prostate cancer patients with gene modified DCs has been recently initiated.